Graphene copper composite wire and preparation method thereof
Through stacked hot pressing, rolling, cutting and cold drawing processes, graphene copper composite conductors were prepared, solving the problems of graphene structural integrity and uniform distribution in the prior art, and achieving high conductivity and high tensile strength.
Patent Information
- Application Number
- CN202411773671.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
During the preparation process, it is difficult for existing graphene copper composite materials to maintain the integrity of the graphene structure and achieve its uniform orientation distribution in the copper matrix, resulting in a far difference in performance from the theoretical value.
Graphene-clad copper foil is used as the basic material, and graphene copper composite conductors are prepared through stacked hot pressing, rolling, cutting and cold drawing processes. The specific steps include hot pressing into blocks in a vacuum hot pressing furnace, rolling into sheets, cutting into strips, and obtaining the final wire by cold drawing and intermediate annealing.
The high conductivity and high tensile strength of graphene copper composite wire are achieved, with conductivity reaching 98-115% IACS, tensile strength reaching 300-370MPa, and elongation above 30%.
Smart Images

Figure CN119581137A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material application, and in particular to a graphene copper composite conductor and a preparation method thereof. Background Art
[0002] Copper is one of the earliest metals used in the history of human civilization and is also the nonferrous metal that has the closest relationship with humans. Pure copper has good ductility and excellent thermal and electrical conductivity. The electrical conductivity of pure copper is 5.8×10 7 s / m (International Annealed Copper Standard IACS), the conductivity of which is second only to silver among all metals (6.3×10 7 s / m), and due to its relatively low cost, copper-based wires are widely used in many fields such as electronics, machinery manufacturing, and aerospace. However, since the discovery of electricity, pure metals have been considered to have the lowest resistivity at room temperature. This assumption defines the upper limit of electricity efficiency and determines the design size and power loss of all traditional electrical machines and equipment. With the rapid development of society and technology, many emerging technology fields have higher and higher requirements for copper wires, especially high-strength and high-conductivity copper wires, and even ultra-high-conductivity copper wires with electrical conductivity exceeding that of pure silver.
[0003] As a member of the carbon material family, graphene was discovered relatively late in the laboratory, but once discovered, it became a research hotspot in the fields of physics and materials due to its special two-dimensional structure and excellent performance. Graphene has high mechanical strength, lower resistivity than silver, and extremely high carrier mobility. It is the material with the best comprehensive performance known so far. Since it is difficult to obtain a single layer of high-quality graphene, graphene is generally filled into the material as a reinforcement. However, there are many problems in doing so. First, there is a strong van der Waals effect between benzene rings. In order to reduce the surface energy, graphene is easy to agglomerate, so it is difficult to make graphene uniformly dispersed in the material, which greatly reduces the uniformity and stability of the composite material performance. Secondly, the wettability between graphene and copper is very poor, and the interface bonding between the two is poor, resulting in reduced material strength. Finally, in the preparation process of the composite material, the structure of graphene is often destroyed, and the excellent performance of graphene strongly depends on the complete structure. Therefore, the performance of the obtained graphene composite material is often far from the theoretical value. However, even so, graphene still has good advantages in improving the mechanical properties of materials and maintaining the high electrical and thermal conductivity of copper.
[0004] Among the current graphene copper preparation methods, the methods that can achieve large-scale preparation generally have difficulty in maintaining the integrity of the graphene structure and achieving the orientation distribution of graphene in the copper matrix; and the preparation methods that can produce graphene copper composite materials with higher performance generally have complicated steps and cannot achieve large-scale preparation of samples. Therefore, if graphene copper composite wires with high strength and high conductivity can be prepared on a large scale, it will have a huge impact on many fields such as electronics, electrical engineering, and mechanical manufacturing. Summary of the invention
[0005] The present invention provides a method for preparing a graphene copper composite wire, which comprises the following steps: S1: Take graphene-coated copper foil, cut it, and stack it into a vacuum hot pressing furnace. Use the hot pressing process to press the multi-layer graphene-coated copper foil into a graphene-copper composite block in a customized mold; S2: rolling the graphene-copper composite block to obtain a graphene-copper composite plate; S3: cutting the graphene copper composite plate into graphene copper strips; S4: cold drawing the graphene copper strip, and performing intermediate annealing during the cold drawing process, so as to obtain a graphene copper composite wire.
[0006] The present invention is further configured as follows: the copper mass fraction of the graphene-coated copper foil in step S1 is greater than 99.95%, the thickness is 10-200 μm, and the number of layers of the laminated hot pressing is 200-1000.
[0007] The present invention is further configured as follows: in step S1, the thickness of the graphene on the graphene-coated copper foil is 0.3-20 nm.
[0008] The present invention is further configured as follows: in step S1, the hot pressing temperature is 950° C. and the hot pressing pressure is 67 MPa.
[0009] The present invention is further configured as follows: in step S2, the rolling direction is parallel to the graphene-coated copper foil laminate interface, so that a complete graphene-copper interface structure is retained during the rolling process.
[0010] The present invention is further configured as follows: the rolling process in step S2 includes rough rolling and finish rolling.
[0011] The present invention is further configured as follows: the rolling rate in step S2 is 2-20 m / min, the deformation amount per pass is 5%-30%, and the thickness of the graphene copper composite plate finally obtained is 1-4 mm.
[0012] The present invention is further configured as follows: the cold drawing in step S4 includes multiple drawing passes, and intermediate annealing is performed during the drawing process; the intermediate annealing treatment temperature is 350-600° C., the treatment time is 30-60 min, and argon gas is used for protection during the annealing process.
[0013] The present invention is further configured as follows: the wire speed of the cold drawing in step S4 is 2-25 m / min, the deformation amount of each pass is 5%-25%, and the diameter of the graphene copper composite wire finally obtained is 0.2-1 mm.
[0014] The present invention also provides a graphene copper composite wire, which is prepared by the preparation method as described above.
[0015] The beneficial effects of the present invention are:
[0016] 1. The present invention uses graphene-coated copper foil as the base material, and through processes such as lamination hot pressing, it can control the preparation of graphene-copper composite blocks with good interface bonding and high conductivity. Compared with the traditional wire forming process, the present invention performs rolling parallel to the direction of the graphene / copper foil lamination to obtain a plate with a low-loss or even lossless interface. The deformation is small during the axial drawing process after cutting, and the degree of damage to the interface due to uniform axial pressure is low, so that the graphene can be continuously distributed in the copper matrix, the interface bonding is good, and the final wire has good electrical and mechanical properties.
[0017] 2. The conductivity of the graphene copper composite wire prepared by the present invention can reach 98-115% IACS; the tensile strength can reach 300-370MPa, and the elongation is above 30%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The conceptual diagram of the present invention is shown.
[0019] Figure 2 A physical flow chart of the present invention is shown. DETAILED DESCRIPTION
[0020] Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0021] Example 1
[0022] The present invention provides a method for preparing a graphene copper composite conductor, comprising the following steps: S1: Take graphene-coated copper foil, cut it, and stack it into a vacuum hot pressing furnace. Use the hot pressing process to press the multi-layer graphene-coated copper foil into a graphene-copper composite block in a customized mold; S2: rolling the graphene-copper composite block to obtain a graphene-copper composite plate; S3: cutting the graphene copper composite plate into graphene copper strips; S4: cold drawing the graphene copper strip, and performing intermediate annealing during the cold drawing process, so as to obtain a graphene copper composite wire.
[0023] The copper mass fraction of the graphene-coated copper foil in step S1 is greater than 99.95%, the thickness is 10-200 μm, and the number of layers of the lamination hot pressing is 200-1000.
[0024] The thickness of the graphene on the graphene-coated copper foil is 0.3-20 nm.
[0025] The hot pressing temperature is 950°C and the hot pressing pressure is 67MPa.
[0026] In step S2, the rolling direction is parallel to the graphene-coated copper foil laminate interface so that a complete graphene-copper interface structure is retained during the rolling process.
[0027] The rolling process includes rough rolling and finish rolling. The rolling rate is 2-20 m / min, the deformation amount of each pass is 5%-30%, and the thickness of the graphene copper composite plate finally obtained is 1-4 mm.
[0028] The cold drawing in step S4 includes multiple drawing passes, and intermediate annealing is performed during the drawing process; the intermediate annealing treatment temperature is 350-600° C., the treatment time is 30-60 min, and argon gas is used for protection during the annealing process.
[0029] The wire speed of cold drawing is 2-25 m / min, the deformation amount of each pass is 5%-25%, and the diameter of the graphene copper composite wire finally obtained is 0.2-1 mm.
[0030] Example 2
[0031] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0032] S1: Take graphene-coated copper foil and cut out 500 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.01 vol %, put the 500 graphene-coated copper foil sheets into a graphite mold, and draw the vacuum degree in a vacuum hot press furnace to 4×10 -4 Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 11 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn, and the conductivity of the graphene copper composite block is measured by an eddy current meter to be 109% IACS.
[0033] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, rough rolling is first used, and the single rolling deformation is 20%. When the graphene copper composite block is rolled to a thickness of less than 6mm, fine rolling is used, and the single rolling deformation is 10%. The rolling rate is 8m / min, and finally a graphene copper composite sheet with a thickness of 2mm is obtained.
[0034] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, use a wire cutting machine to cut the graphene copper composite sheet into 2×2 mm square bars, that is, to obtain graphene copper bars, and deburr and clean the cut graphene copper bars.
[0035] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap base or synthetic lubricant is used to reduce friction and prevent damage to the wire surface. The deformation of each pass is 15%, and the wire speed is 9m / min. When the diameter is pulled to 1mm, an intermediate annealing treatment is performed at a temperature of 450℃ for 30min. Finally, a graphene copper composite wire with a diameter of 0.5mm is obtained. The conductivity is measured by the four-wire method to be 106.6% IACS and the tensile strength is 342.4MPa.
[0036] Example 3
[0037] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0038] S1: Take graphene-coated copper foil and cut out 800 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.01 vol%. Put the 800 graphene-coated copper foil sheets into a graphite mold and draw the vacuum degree in a vacuum hot pressing furnace to 4×10 -4Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 17.5 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn, and the conductivity of the graphene copper composite block is measured by an eddy current meter to be 108.2% IACS.
[0039] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, the rough rolling method is first used, and the single rolling deformation is 20%. When the thickness of the graphene copper composite block is rolled to less than 6mm, the fine rolling is used, and the single rolling deformation is 10%. The rolling rate is 8m / min, and finally a graphene copper composite plate with a thickness of 3mm is obtained.
[0040] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, cut the graphene copper composite sheet into 3×3 mm square bars using a wire cutting machine, that is, prepare graphene copper bars, and deburr and clean the cut graphene copper bars.
[0041] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap base or synthetic lubricant is used to reduce friction and prevent damage to the wire surface. The deformation of each pass is 15%, and the wire speed is 9m / min. When the diameter is pulled to 1mm, an intermediate annealing treatment is performed at a temperature of 450℃ for 30min. Finally, a graphene copper composite wire with a diameter of 0.5mm is obtained. The conductivity is measured to be 104.3%IACS using the four-wire method, and the tensile strength is 321.1MPa.
[0042] Example 4
[0043] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0044] S1: Take graphene-coated copper foil and cut out 500 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.001 vol%. Put the 500 graphene-coated copper foil sheets into a graphite mold and draw the vacuum degree in a vacuum hot press furnace to 4×10 -4Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 11 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn. The conductivity of the graphene copper composite block is measured by an eddy current meter and is 101.4% IACS.
[0045] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, the rough rolling method is first used, and the single rolling deformation is 20%. When the thickness of the graphene copper composite block is rolled to less than 6mm, the fine rolling is used, and the single rolling deformation is 10%. The rolling rate is 8m / min, and finally a graphene copper composite plate with a thickness of 2mm is obtained.
[0046] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, use a wire cutting machine to cut the graphene copper composite sheet into 2×2 mm square bars, that is, to obtain graphene copper bars, and deburr and clean the cut graphene copper bars.
[0047] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap base or synthetic lubricant is used to reduce friction and prevent damage to the wire surface. The deformation of each pass is 15%, and the wire speed is 9m / min. When the diameter is pulled to 1mm, an intermediate annealing treatment is performed at a temperature of 450℃ for 30min. Finally, a graphene copper composite wire with a diameter of 0.5mm is obtained. The conductivity is 99.7%IACS and the tensile strength is 335.7MPa measured by the four-wire method.
[0048] Example 5
[0049] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0050] S1: Take graphene-coated copper foil and cut out 500 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.01 vol %, put the 500 graphene-coated copper foil sheets into a graphite mold, and draw the vacuum degree in a vacuum hot press furnace to 4×10 -4Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 11 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn. The conductivity of the graphene copper composite block is measured by an eddy current meter and is 112.2% IACS.
[0051] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, the rough rolling method is first used, and the single rolling deformation is 15%. When the thickness of the graphene copper composite block is rolled to less than 6mm, the fine rolling is used, and the single rolling deformation is 5%. The rolling rate is 5m / min, and finally a graphene copper composite plate with a thickness of 2mm is obtained.
[0052] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, use a wire cutting machine to cut the graphene copper composite sheet into 2×2 mm square bars, that is, to obtain graphene copper bars, and deburr and clean the cut graphene copper bars.
[0053] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap base or synthetic lubricant is used to reduce friction and prevent damage to the wire surface. The deformation of each pass is 15%, and the wire speed is 9m / min. When the diameter is pulled to 1mm, an intermediate annealing treatment is performed at a temperature of 450℃ for 30min. Finally, a graphene copper composite wire with a diameter of 0.5mm is obtained. The conductivity is measured to be 108.5% IACS using the four-wire method, and the tensile strength is 352.0MPa.
[0054] Example 6
[0055] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0056] S1: Take graphene-coated copper foil and cut out 500 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.01 vol %, put the 500 graphene-coated copper foil sheets into a graphite mold, and draw the vacuum degree in a vacuum hot press furnace to 4×10 -4Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 11 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn, and the conductivity of the graphene copper composite block is measured by an eddy current meter to be 104.9% IACS.
[0057] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, the rough rolling method is first used, and the single rolling deformation is 20%. When the thickness of the graphene copper composite block is rolled to less than 6mm, the fine rolling is used, and the single rolling deformation is 10%. The rolling rate is 8m / min, and finally a graphene copper composite plate with a thickness of 2mm is obtained.
[0058] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, use a wire cutting machine to cut the graphene copper composite sheet into 2×2 mm square bars, that is, to obtain graphene copper bars, and deburr and clean the cut graphene copper bars.
[0059] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap base or synthetic lubricant is used to reduce friction and prevent damage to the wire surface. The deformation of each pass is 25%, and the wire speed is 10m / min. When the diameter is pulled to 1mm, an intermediate annealing treatment is performed at a temperature of 450℃ for 30min. Finally, a graphene copper composite wire with a diameter of 0.5mm is obtained. The conductivity is measured by the four-wire method to be 103.5% IACS and the tensile strength is 347.9MPa.
[0060] Example 7
[0061] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0062] S1: Take graphene-coated copper foil and cut out 500 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.01 vol %, put the 500 graphene-coated copper foil sheets into a graphite mold, and draw the vacuum degree in a vacuum hot press furnace to 4×10 -4Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 11 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn. The conductivity of the graphene copper composite block is measured by an eddy current meter and is 108.8% IACS.
[0063] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, the rough rolling method is first used, and the single rolling deformation is 20%. When the thickness of the graphene copper composite block is rolled to less than 6mm, the fine rolling is used, and the single rolling deformation is 10%. The rolling rate is 8m / min, and finally a graphene copper composite plate with a thickness of 2mm is obtained.
[0064] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, use a wire cutting machine to cut the graphene copper composite sheet into 2×2 mm square bars, that is, to obtain graphene copper bars, and deburr and clean the cut graphene copper bars.
[0065] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap base or synthetic lubricant is used to reduce friction and prevent damage to the wire surface. The deformation of each pass is 15%, and the wire speed is 9m / min. When the diameter is pulled to 1mm, an intermediate annealing treatment is performed at a temperature of 550℃ for 60min. Finally, a graphene copper composite wire with a diameter of 0.5mm is obtained. The conductivity is measured to be 109.2%IACS using the four-wire method, and the tensile strength is 306.2MPa.
[0066] Example 8
[0067] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0068] S1: Take graphene-coated copper foil and cut out 500 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.01 vol %, put the 500 graphene-coated copper foil sheets into a graphite mold, and draw the vacuum degree in a vacuum hot press furnace to 4×10 -4Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 11 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn. The conductivity of the graphene copper composite block is measured by an eddy current meter and is 100.1% IACS.
[0069] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, the rough rolling method is first used, and the single rolling deformation is 20%. When the thickness of the graphene copper composite block is rolled to less than 6mm, the fine rolling is used, and the single rolling deformation is 10%. The rolling rate is 8m / min, and finally a graphene copper composite plate with a thickness of 2mm is obtained.
[0070] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, use a wire cutting machine to cut the graphene copper composite sheet into 2×2 mm square bars, that is, to obtain graphene copper bars, and deburr and clean the cut graphene copper bars.
[0071] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap or synthetic lubricants are used to reduce friction and prevent wire surface damage. The deformation of each pass is 15% and the wire speed is 9m / min. Finally, a graphene copper composite wire with a diameter of 0.8mm is obtained. The conductivity is 98.2% IACS and the tensile strength is 368.7MPa measured by the four-wire method.
[0072] Example 9
[0073] This embodiment adopts the preparation method disclosed in Example 1 to prepare the graphene copper composite wire, wherein the graphene-coated copper foil is a purchased item, and the specific preparation process is as follows:
[0074] S1: Take graphene-coated copper foil and cut out 500 graphene-coated copper foil sheets with a diameter of 30 mm, in which the volume proportion of graphene is 0.01 vol %, put the 500 graphene-coated copper foil sheets into a graphite mold, and draw the vacuum degree in a vacuum hot press furnace to 4×10 -4 Pa, set the hot pressing temperature to 950°C, the holding time to 40 min, the hot pressing pressure to 67 MPa, the holding time to 60 min, and take it out after cooling to room temperature to obtain a graphene copper composite block with a height of 11 mm and a diameter of 30 mm. Use 600, 1200, 2000, and 3000 mesh sandpaper to polish it in turn, and the conductivity of the graphene copper composite block is measured by an eddy current meter to be 109.2% IACS.
[0075] S2: After cleaning, grinding and polishing the graphene copper composite block, send it to the cold rolling mill for rolling, and the rolling direction is set parallel to the laminate interface direction, so that the complete graphene copper interface structure can be retained. During rolling, the rough rolling method is first used, and the single rolling deformation is 20%. When the thickness of the graphene copper composite block is rolled to less than 6mm, the fine rolling is used, and the single rolling deformation is 10%. The rolling rate is 8m / min, and finally a graphene copper composite plate with a thickness of 2mm is obtained.
[0076] S3: Fix the prepared graphene copper composite sheet on a workbench to ensure the stability of the workpiece, use a wire cutting machine to cut the graphene copper composite sheet into 2×2 mm square bars, that is, to obtain graphene copper bars, and deburr and clean the cut graphene copper bars.
[0077] S4: The graphene copper strip is drawn multiple times. During the drawing process, soap base or synthetic lubricant is used to reduce friction and prevent damage to the wire surface. The deformation of each pass is 5%, and the wire speed is 2m / min. When the diameter is pulled to 1mm, an intermediate annealing treatment is performed at a temperature of 550℃ for 60min. Finally, a graphene copper composite wire with a diameter of 0.2mm is obtained. The conductivity is measured to be 111.2% IACS using the four-wire method, and the tensile strength is 330.7MPa.
[0078] The specific parameters of Examples 2-9 are described in Table 1: Table 1. Experimental parameters of the method of Example 1
[0079] Referring to the data in Table 1, it can be seen that the number of graphene copper layers, rolling and drawing deformation, rolling and drawing rate, annealing temperature and time all have a significant effect on the performance of graphene copper composite wires. In Example 3, the number of graphene-coated copper foil layers is increased compared with Example 2, the density of the graphene copper composite block is reduced, and the conductivity and tensile strength are reduced accordingly; in Example 4, the graphene thickness on the graphene-coated copper foil is reduced compared with Example 2, the volume ratio is reduced, the conductivity is significantly reduced, and the tensile strength is slightly affected, indicating that the content of graphene has an important influence on the conductivity; in Example 5, compared with Example 2, the deformation amount per rolling pass is reduced, the degree of deformation is reduced, the degree of damage to the graphene and copper interlayer structure is reduced, the conductivity is increased, and the tensile strength is less affected. In Example 6, compared with Example 2, the deformation amount per drawing pass is increased, the degree of deformation is increased, the degree of damage to the graphene and copper interlayer structure is increased, the conductivity is reduced, and the tensile strength is less affected; in Example 7, the annealing temperature and time are increased, the tensile strength is reduced, and the conductivity is improved.
[0080] Example 10
[0081] This embodiment discloses a highly conductive graphene copper composite wire, which is prepared by the preparation method described in Example 1.
[0082] In summary, the present invention uses graphene-coated copper foil as the base material, and through processes such as lamination and hot pressing, it can control the preparation of graphene-copper composite blocks with good interface bonding and high electrical conductivity. Compared with the traditional wire forming process, the present invention performs rolling parallel to the direction of the graphene / copper foil lamination to obtain a plate with a low-loss or even lossless interface. The deformation amount is small during the axial drawing process after cutting, and the degree of damage to the interface due to uniform axial pressure is low, so that the graphene can be continuously distributed in the copper matrix, the interface bonding is good, and the final wire has good electrical and mechanical properties. The conductivity of the graphene-copper composite wire prepared by the present invention can reach 98-115% IACS; the tensile strength can reach 300-370MPa, and the elongation is above 30%.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be within the scope of protection of the present invention.
Claims
1. A method for preparing a graphene copper composite wire, characterized in that: The following steps are included: S1: Take graphene-coated copper foil, cut it, and stack it into a vacuum hot pressing furnace. Use the hot pressing process to press the multi-layer graphene-coated copper foil into a graphene-copper composite block in a customized mold; S2: rolling the graphene-copper composite block to obtain a graphene-copper composite plate; S3: cutting the graphene copper composite plate into graphene copper strips; S4: cold drawing the graphene copper strip, and performing intermediate annealing during the cold drawing process, so as to obtain a graphene copper composite wire.
2. The method for preparing the graphene copper composite wire according to claim 1, characterized in that: The copper mass fraction of the graphene-coated copper foil in step S1 is greater than 99.95%, the thickness is 10-200 μm, and the number of layers of the laminated hot pressing is 200-1000.
3. The method for preparing the graphene copper composite wire according to claim 1, characterized in that: The thickness of the graphene on the graphene-coated copper foil in step S1 is 0.3-20 nm.
4. The method for preparing a graphene copper composite wire according to claim 1, characterized in that: In step S1, the hot pressing temperature is 950° C. and the hot pressing pressure is 67 MPa.
5. The method for preparing a graphene copper composite wire according to claim 1, characterized in that: In step S2, the rolling direction is parallel to the graphene-coated copper foil laminate interface so that a complete graphene-copper interface structure is retained during the rolling process.
6. The method for preparing a graphene copper composite wire according to claim 1, characterized in that: The rolling process in step S2 includes rough rolling and finish rolling.
7. The method for preparing a graphene copper composite wire according to claim 1, characterized in that: The rolling rate in step S2 is 2-20 m / min, the deformation amount in each pass is 5%-30%, and the thickness of the graphene copper composite sheet finally obtained is 1-4 mm.
8. The method for preparing a graphene copper composite wire according to claim 1, characterized in that: The cold drawing in step S4 includes multiple drawing passes, and intermediate annealing is performed during the drawing process; the intermediate annealing treatment temperature is 350-600° C., the treatment time is 30-60 min, and argon gas is used for protection during the annealing process.
9. The method for preparing a graphene copper composite wire according to claim 1, characterized in that: The wire speed of cold drawing in step S4 is 2-25 m / min, the deformation amount of each pass is 5%-25%, and the diameter of the graphene copper composite wire finally obtained is 0.2-1 mm.
10. A highly conductive graphene copper composite wire, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Graphene copper-based composite material and preparation method and application thereof
CN113695394A
Preparation method of high-strength and high-conductivity copper / graphene composite material
CN113752666A
Graphene copper wire, preparation method thereof and cable
CN114388167A
Preparation method of high-conductivity graphene / copper composite wire
CN117079890A
Preparation method of high-conductivity graphene copper composite material
CN118910548A
Cited By
Three-dimensional graphene copper composite material based on in-situ interface chemical bonding and preparation method and application thereof
CN121294932A